From Theory to Practice: The Pedagogic Application of Major L2 Motivation Theories in an IB School - Marwan, Hesty Ferdalina (Journal of English and Education (JEE), 2022)
Motivation is believed to play a vital role in successful second language (L2) learning. Over the past five decades, L2 motivation theory has evolved significantly from static to more dynamic perspectives. This article reviews the four major second language (L2) motivation research phases (i.e., the social psychological period, the cognitive-situated period, the process-oriented period and the current socio-dynamic period); and contemplates the application of some motivational models that are relevant to a specific pedagogical context in an International Baccalaureate (IB), bilingual school in Indonesia, such as such as the instrumental motivation, the process-oriented model, the L2 Motivational Self System, and motivational teaching practices.